Analytical characterization of "etonitazepyne, " a new pyrrolidinyl‐containing 2‐benzylbenzimidazole opioid sold online. Issue 9 (19th June 2021) - Blanckaert, Peter; Balcaen, Margot; Vanhee, Céline; Risseeuw, Martijn; Canfyn, Michaël; Desmedt, Bart; Van Calenbergh, Serge; Deconinck, Eric
Abstract: This paper reports on the identification and full chemical characterization of the substance colloquially called "etonitazepyne" or " N ‐pyrrolidino etonitazene" (2‐(4‐ethoxybenzyl)‐5‐nitro‐1‐(2‐(pyrrolidin‐1‐yl)ethyl)‐1 H ‐benzo[ d ]imidazole), a potent NPS opioid of the 5‐nitrobenzimidazole class. Identification of etonitazepyne was performed, on a sample purchased during routine monitoring of the drug market, using GC‐MS, HRAM LC‐MS/MS, 1 H NMR, and FTIR. The chromatographic data, together with the FTIR data, indicated the presence of a highly pure compound and already indicated a benzimidazole structure. The specific benzimidazole regio‐isomer was confirmed using 1 H NMR spectroscopy, resulting in the unambiguous identification of etonitazepyne. Abstract : This paper reports on the identification and full chemical characterization of etonitazepyne (2‐(4‐ethoxybenzyl)‐5‐nitro‐1‐(2‐(pyrrolidin‐1‐yl)ethyl)‐1 H ‐benzo[d]imidazole), a potent NPS opioid of the 5‐nitrobenzimidazole class. Identification of etonitazepyne was performed using GC‐MS, HRAM LC‐MS/MS, 1 H NMR, and FTIR. The analytical data resulted in the unambiguous identification of etonitazepyne as a single, highly pure compound. In addition to a public health risk, these opioids present a challenge for toxicological and forensic laboratories, who might not be able to identify these new substances.